Development of a Simulated Method for Continuous Monitoring of Radiation in the Nuclear Medicine Department (Wad Medani) - M.S. Zobly, Sulieman; I. Omer, Abdu (Gezira Journal of Engineering and Applied Sciences, 2021)
Generally, radiations emit from different sources of energy. Some of these radiations are very dangerous. They may lead to many diseases like cancer. Many nuclear institutes over the world have been established for the purpose of diagnostic and treating by using radioisotopes. The optimization of staff protection  is  essential  in  the  nuclear  medicine  department to minimize  the  effect of  the radiation to the department staff  and to other people. In  all  around the world, detectors are used to monitor the radiation.       This paper is discussing a microcontroller simulated system; the system was established by situating four detectors in the department of nuclear medicine to monitor the injected patients with Tc 99 m . Gamma photons are converted into pulses at the output of the detectors, and then they are transmitted to the microcontroller to define the radiated area. If any of this injected patient inter to a non-radiated area, the detector issues an alarm and red colour in the monitoring room. Moreover, the area number is displayed in the liquid cathode display (LCD) of the microcontroller.